GAS WELL DELIVERABILITY IN X FIELD BASED ON DATA FIELD - PRASETYO (NIM : 12299048), HARI
In Gas contract, there are two main points which should be satisfied by the contractor to the client. They are flow rate (plateau flow rate and constant flow rate), and adequate pressure for gas transportation. The X field is a dry gas reservoir with several productive zones. Each well produces from the fact that two zones. The well produces from more than one layer or zone, dual tubing and tubing-annulus combination are selected as well completion systems. In this final project, the value of plateau flow rate from each layer is combined in order to achieve 10 MMscfd total plateau flow rate with the longest time and the same plateau duration for all wells. Scenario conducted in this study uses compressors to maintain plateau flow rate. The Reservoir performance is predicted using material balance p/z vs Gp method and gas deliverability is predicted using Rawlins-Schellhardt equation. The assumption of these methods are single gas phase, tank model, depletion drive mechanism, and isothermal.